Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1532-950x.1993.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Loss of Tensile Strength and Elasticity of Five Absorbable Suture Materials in Sterile and Infected Canine Urine

Abstract: The loss of breaking strength and elasticity of five absorbable suture materials (polydioxanone [PDS-II], polyglycolic acid [PGA], polyglactin 910 [PG-910], polyglyconate [GTMC], and chromic gut) after in vitro incubation in sterile, Escherichia coli- and Proteus mirabilis-inoculated canine urine was studied. Biomechanical testing, in a controlled environment, was performed during the 28-day study period. Polydioxanone and chromic gut retained greater than 90% of their original strengths after 28 days of incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…A knot-tensioning load or force is reported in few investigations reviewed (e.g. 1.5 kg [Rosin & Robinson, 1989], 1 N [Schiller et al, 1993], 7 N [Nilsson, 1982], and 9 N [Holmlund, 1974]). Results from a trial involving 10 surgeons tying sutures around synthetic tissue did not include values for the knot-tensioning loads, but in the subsequent investigation knots were tensioned with a force of 10 N (Annunziata et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A knot-tensioning load or force is reported in few investigations reviewed (e.g. 1.5 kg [Rosin & Robinson, 1989], 1 N [Schiller et al, 1993], 7 N [Nilsson, 1982], and 9 N [Holmlund, 1974]). Results from a trial involving 10 surgeons tying sutures around synthetic tissue did not include values for the knot-tensioning loads, but in the subsequent investigation knots were tensioned with a force of 10 N (Annunziata et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…In the cut-loop method a loop is formed as in the loop method, however the knotted suture loop is cut opposite the knot and each newly formed end is placed in a jaw of a tensile tester (Huber et al, 1999;Lewis, Milthorpe, & Bellenger, 1997;Rodeheaver, Green, Odum, Bussard, & Edlich, 1998;Rosin & Robinson, 1989;Schiller, Stone, & Gupta, 1993;Tera & Aberg, 1976a;Thacker et al, 1975). Although the load is applied to the patient's side, the cutloop technique usually measures knot slippage rather than knot strength, the measured values being affected by the length of the ears.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Bacteria such as Proteus spp should theoretically cause greater suture degradation through urease-splitting action to produce ammonia, which accelerate destruction of absorbable suture materials that undergo hydrolysis. 5,8 However, the data obtained from this study suggested slightly greater suture materials degradation in an E coli inoculated medium than a Proteus inoculated medium.…”
Section: Discussionmentioning
confidence: 99%
“…5 Polydioxanone Polydioxanone (PDS) or poly-p-dioxanone is a slowly absorbable monofilament suture composed of the polyester, poly (p-dioxanone). It is naturally degraded in the body by hydrolysis and has approximately 60% strength left at 14 days; absorption is completed between 60 and 90 days.…”
Section: Non-absorbable Suture Materialsmentioning
confidence: 99%
“…5 It is biologically inert and can easily be sterilized by autoclaving. Steel has the highest strength of any other suture material.…”
Section: Stainless Steelmentioning
confidence: 99%